Kajian Sistematis: Pengaruh Durasi Tidur Terhadap Performa Akademik Mahasiswa Perguruan Tinggi - Zega, Ester Ratna Cahyani; Zega, Metalitas (CV. SINAR HOWUHOWU, 2025)
This systematic review examines the relationship between sleep duration and academic performance among university students. Through a comprehensive analysis of 52 studies published between 2014-2024, involving 43,675 students across 31 countries, we investigated the complex interactions between sleep patterns and academic achievement. Using the PRISMA methodology and quality assessment tools, we analyzed various aspects of sleep duration, including weekday/weekend patterns, sleep quality, and their impact on cognitive performance and academic outcomes. Results demonstrate a significant correlation between optimal sleep duration (7-9 hours) and improved academic performance (r = 0.48, p < 0.001), with notable variations across different academic disciplines and study environments. The findings highlight the critical role of sleep hygiene in academic success and provide evidence-based recommendations for university health policies and student wellness programs.